Między średnią a późną dorosłością – zajęcia dla „seniorów 50+” - Sienkiewicz-Wilowska, Julia Anastazja (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article analyzes occurrences related to conducting classes for “seniors 50+”, targets of the design of such an offer and the strengths and weaknesses of this approach. These issues are considered in the context of the theory associated with aging, as well as with the changes which are taking place in society. In conclusion it has been shown that these activities can play a preventive and developmentoriented function.